Finite time adaptive filter control of nonlinear systems with actuator faults and state constraints. Issue 2 (5th October 2022) - Zhang, Huiyun; Wu, Libing; Yan, Weijun; Hu, Yuhan
Abstract: The finite time adaptive filter control problem is studied for strict‐feedback nonlinear systems with actuator faults and state constraints in this paper. First, with the aid of the backstepping technique, the controller and the adaptive laws are designed to compensate the actuator faults and parameter uncertainties. Then, the dynamic surface control is used to establish a first‐order filter to alleviate computational burden for the reason of the derivative of virtual control laws. In addition, none of the system states violate predefined constraint boundaries by utilizing a log‐type barrier Lyapunov function. Furthermore, the boundedness can be ensured for all the closed‐loop signals, and better tracking performance of the system is obtained within a finite‐time. Finally, the simulation examples are shown to prove the feasibility and effectiveness of the proposed strategy.